Análise da integridade estrutural de compósitos através da caracterização fractal de sinais de emissão acústica - Silva, Francisco Estênio da (2002)
In this work it is analysed the mechanical integrity of the composite material constituted of a polymeric matrix, epoxy resin DER 331, reinforced by glass fiber type E. This analysis has been done by using the acoustic emission testing with the aim to correlating the wave-form of the pulse with the flaw mechanisms associated to the tensile and bending loads applied to the samples. The analysis of the pulses as a function of time has been made by using box counting method, which provides the fractal dimension, and the rescaled Hurst analysis. The analysis in the frequency domain has been made by using the spectral Fourier method It has been shown that the exponents obtained from the spectral Fourier method and the rescaled Hurst analysis are correlated to the box counting fractal dimension, and satisfy the known relations obtained from the scaling laws. The results have also shown the existence of two scaling regions, characterized by the persistence of the pulse and by a random behaviour, respectively. The fractal dimensions have also been shown to be independent of time acquisition of the emitted pulse, and this indication of self-similarity confirms its fractal characteristics. Finally, it is conjectured a correlation between the Hurst coefficient/fractal dimension and the mechanical flaws observed.